Սուլթանական կառավարության ազգային քաղաքականությունը Արևմտյան Հայաստանի մահմեդական բնակչության նկատմամբ (1898-1908 թթ.) - Համբարյան, Ազատ («Զանգակ - 97»)
Based on unpublished archival materials and other primaiy sources, author considers some peculiarities of politics of Ottoman sultan Abdul Hamid II toward the Muslim population of Western Armenia, namely Kurds, Türks, North Caucasians. The Muslims of Ottoman Empire were regarded by the bloody tyrant as the basis of regime and as allies in the struggle against Armenien national-liberation movement. Author coneludes that this politics of oppressive Turkish govemment was aimed to increase the percentage of Muslim population, in paiticular Türks, regarding the Armenians.
Keywords: Հայոց պատմություն